2020
DOI: 10.1108/itp-07-2019-0366
|View full text |Cite
|
Sign up to set email alerts
|

Improving mobile health apps usage: a quantitative study on mPower data of Parkinson's disease

Abstract: PurposeThe emergence of mobile health (mHealth) products has created a capability of monitoring and managing the health of patients with chronic diseases. These mHealth technologies would not be beneficial unless they are adopted and used by their target users. This study identifies key factors affecting the usage of mHealth apps based on user usage data collected from an mHealth app.Design/methodology/approachUsing a dataset collected from an mHealth app named mPower, developed for patients with Parkinson's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Largely, the TOE framework has Kouhizadeh et al (2021) who used the TOE framework approach to explore the challenges and as a whole beyond the individual perspective. Though this approach differs from the work of level (Li and Chang, 2020;Patil et al 2020). TOE framework takes a view of the organisation their basis to study the challenges and opportunities of technology adoption at the individual Previous studies have used various technology adoption theories such as TAM, UTAUT etc as facilitators, importantly, these include environment or government regulatory, infrastructures human capital size; and environment context refers to certain operational inhibitors and describes top management, the resources of the firm such internal tool and specialisation, represents the availability and the features of technological innovation; organisation context 1 5 that include technology support by connecting to technology consultants in quality ICT.…”
Section: Technological -Organisational -Environmental (Toe)mentioning
confidence: 95%
See 2 more Smart Citations
“…Largely, the TOE framework has Kouhizadeh et al (2021) who used the TOE framework approach to explore the challenges and as a whole beyond the individual perspective. Though this approach differs from the work of level (Li and Chang, 2020;Patil et al 2020). TOE framework takes a view of the organisation their basis to study the challenges and opportunities of technology adoption at the individual Previous studies have used various technology adoption theories such as TAM, UTAUT etc as facilitators, importantly, these include environment or government regulatory, infrastructures human capital size; and environment context refers to certain operational inhibitors and describes top management, the resources of the firm such internal tool and specialisation, represents the availability and the features of technological innovation; organisation context 1 5 that include technology support by connecting to technology consultants in quality ICT.…”
Section: Technological -Organisational -Environmental (Toe)mentioning
confidence: 95%
“…Moreover, hydroelectric dams in required to manage one Bitcoin transaction is equal to that required to power nine households to Siegfried et al (2020) andO' Leary (2018). Similarly, it has been reported that the energy 2020a) has been compared to the electricity consumption in the country of Ireland according a consensus algorithm (Nakamoto, 2008), the energy that Bitcoin consumes (Chang et al 2020;Min, 2019). Since blockchain technology underpins bitcoins and uses Proof of Work as as an extent of computing resources and energy consumption (O'Leary, 2017; Kumar et al…”
Section: Wasted Resources or Energy Consumption Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, and more specifically, healthcare m-apps (sometimes called mHealth apps) have attracted the interest of researchers and practitioners from various disciplines, representing a relatively new area (Li and Chang, 2020) that has implications on the micro (patients and healthcare providers) and on the macro level (healthcare industry and the economy) (Mansour, 2017).…”
Section: -1 Background: Mobile Apps (M-apps)mentioning
confidence: 99%
“…2-2-1-1 Perceived Ease of Use Generally, a new technology will have no value if not adopted by its target users (Li and Chang, 2020). Clearly, it is adopted if an individual perceives its benefits (Vahdat et al, 2020).…”
Section: -2-1 Antecedents To M-apps Use Intentionmentioning
confidence: 99%